Debt financing behaviour of Shariah compliant SMEs (enterprise 50). A dynamic approach on Malaysian Islamic capital market - Haron, Razali (2015)

(untitled)
Employing a dynamic approach, this study investigates the debt financing behaviour of Shariah compliant E50 SMEs in Malaysia covering the existence of target debt, speed of adjustment, factors affecting the adjustment speed and the rational financing behaviour for the period of 2009-2013. This study is motivated by the outstanding growth of Islamic Capital Market (ICM) which has increased by 22.6% to RM1.4 trillion and is expected to reach RM 2.9 trillion by 2020. With the establishment of Shariah Advisory Council (SAC), Securities Commission of Malaysia has set up certain standard of parameters as guidelines in classifying Shariah compliant securities. The central features of the Shariah compliant securities are the prohibition of activities that involve interest (riba), gambling (maisir), uncertainties and speculative trading (gharar). Periodical monitoring is carried out to ensure continuous conformity of those firms to the Shariah principles.